Neurobiomechanical Effects of Fatigue on Climbing Performance and Injury Risk - Szredzka, Aleksandra; Skowrońska-Borsuk, Julia; Borsuk, Adam; Sposób, Julia; Czerwiec, Bartłomiej; Narożniak, Martyna; Pękacka, Adrianna; Wojtas, Malwina; Krupa, Zuzanna; Pergoł, Joanna (Quality in Sport, 2025)
Introduction and Purpose: Sport climbing poses significant physical and neuromuscular demands, with muscular fatigue representing a critical factor affecting performance, technique, and injury susceptibility. As climbing participation increases, understanding the medical implications of fatigue becomes essential. This review explores how central and peripheral muscle fatigue influence motor coordination, climbing biomechanics, and injury risk, from a neurophysiological and biomechanical perspective. Current Knowledge: Central fatigue disrupts motor unit recruitment by impairing central nervous system output, while peripheral fatigue compromises muscle fiber contractility. Both forms of fatigue degrade proprioception, coordination, and postural control, leading to inefficient movement and increased mechanical load on joints and tendons. Fatigue-related motor impairments contribute to a higher incidence of overuse injuries—particularly affecting the fingers, shoulders, and knees—and increase the likelihood of falls due to delayed reaction time and impaired decision-making. Although experienced climbers exhibit compensatory strategies, these adaptations are not sufficient to mitigate all health risks. Conclusion: Muscle fatigue is a significant medical concern in sport climbing, with direct implications for musculoskeletal injury and neuromotor control. Preventive strategies should involve targeted conditioning, fatigue monitoring (e.g., HRV, RPE), and early identification of biomechanical compensations. Further interdisciplinary research is needed to inform evidence-based guidelines for injury prevention, especially in novice and youth climbers.